Endoscopic Retrieval Technique of Proximally Migrated Pancreatic Stents: A Retrospective Study in a Tertiary Centre - Yi Lu; Zheng Jin; Jia-chuan Wu; Li-ke Bie; Biao Gong (Gastroenterology Research and Practice)
Background. There were scarce trials concerning the treatments and outcomes of proximal pancreatic stent migration. Herein, we did a retrospective study to discuss this problem from an endoscopist’s point of view. Patients and Methods. From January 2009 to June 2014, patients with proximally migrated pancreatic duct stents were identified. Their clinical information was viewed. Retrieval techniques, success rates, and adverse events were analyzed. Results. A total of 36 procedures were performed in 34 patients; the median age of the patients was 53 years, with 17 males and 17 females. Eight patients’ pancreatic duct stents could still be seen in the major or minor papilla and were pulled out with a snare forceps or a grasping forceps; in the remaining 28 procedures, the management was somewhat thorny; the retrieval called for several devices. Final success was achieved in 31 patients. No adverse event was observed in the process of ERCP procedures, 5 patients developed post-ERCP pancreatitis (PEP), 1 patient got infection, and 1 patient had haemorrhage. Conclusions. Endoscopic retrieval of migrated pancreatic stent is safe and less invasive; nonetheless, attention should be paid so as to reduce the incidence and degree of related adverse events, especially PEP.